Alat Ukur Berat Badan dengan Tinggi Badan yang Disertai dengan Pengukuran IMT (Indeks Massa Tubuh) Sebagai Pendeteksi Obesitas pada Remaja - Haidar Ahmad Musyaffa; Anis Prabowo; Ipin Prasojo; Retno Dewi Noviyanti (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
The obesity rate among adolescents in Indonesia is increasingly worrying. Obesity in adolescents is affected by a variety of factors, including lifestyle changes that tend to lead to an unhealthy diet and lack of physical activity. To overcome this problem, early prevention efforts are very important, one of which is by measuring Body Mass Index (BMI) as an early indicator of obesity. This research uses a Research and Development (RnD) approach, which aims to develop or improve existing tools to obtain new data and insights into the use of these tools in various contexts. This tool is a development of the previous tool with the HC SR04 sensor to measure height, the Load Cell sensor to measure weight, and the Atmega328p microcontroller to calculate BMI. The main innovation of the tool is the use of a 433 MHz Radio Frequency module that allows wireless communication between height and weight data, increasing the mobility of the tool as it does not require cables and poles as a support. With the result of an error value in the IMT measurement of 1,28%. With an error value of 1.28% in BMI measurements and 93.40% in BMI measurement validity. So from the results of the above percentage, it can be stated that this tool is suitable for use.